Potential Economic Benefits of Paid Sick Leave in Reducing Absenteeism Related to the Spread of Influenza-Like Illness. Issue 9 (September 2017) - Asfaw, Abay; Rosa, Roger; Pana-Cryan, Regina
Abstract : Objective: Most U.S. employers are not required to provide paid sick leave (PSL), and there is limited information on the economic return of providing PSL. We estimated potential benefits to employers of PSL in reducing absenteeism related to the spread of influenza-like illness (ILI). Methods: We used nationally representative data and a negative binomial random effects model to estimate the impact of PSL in reducing overall absence due to illness or injury. We used published data to compute the share of ILI from the total days of absence, ILI transmission rates at workplaces, wages, and other parameters. Results: Providing PSL could have saved employers 0.63 to 1.88 billion in reduced ILI-related absenteeism costs per year during 2007 to 2014 in 2016 dollars. Conclusion: These findings might help employers consider PSL as an investment rather than as a cost without any return.